PENYULUHAN MENGENAI AKTIVITAS PERGUDANGAN PAD PT CORINTHIAN INDUSTRIES INDONESIA - M Tirtana Siregar; Dadang Arjuna (ABDI KAMI: Jurnal Pengabdian Kepada Masyarakat, 2020)
Warehousing is all activities that include receiving, storing, maintaining, distributing, controlling and reporting logistics and logistics equipment so that quality and quantity are guaranteed. This research was conducted directly in the warehouse section of PT Corinthian Industries Indonesia (CII), which wanted to implement a warehouse activity process using the checklist document on material acceptance and procedure for dispensing goods. Methods of data collection include observation, communication, and documentation. Proposals that can be done are in the form of improving warehousing activities that are adjusted to the actual conditions of the company. With these improvements the company can prevent losses caused by problems that occur. That way, a continuous improvement approach can be made.